Juvenile fibromyalgia: Guidance for management. Issue 4 (5th August 2013) - Yokota, Shumpei; Kikuchi, Masako; Miyamae, Takako
Abstract: Juvenile fibromyalgia (JFM) is a disease in which patients complain of acute and chronic severe pain, an overt primary cause for which cannot be found or surmised. Although patients with JFM mainly complain of systemic pain or allodynia in the medical interview and physical examination, the concept of the disease is the total sum of painful illness, chronic fatigue, hypothermia and many other autonomic symptoms and signs. Many issues are interacting including individual traits (personality, temperament, sensitivity, memory of pain; age: early adolescence), individual states (self‐esteem, anxiety, developmental level), and external stressors (parent especially mother, school environment). JFM is diagnosed on the combination of disease history, physical examination to determine the 18 tender points and allodynia, pain from gently touching their hair, and negative results of blood tests (inflammatory markers, thyroid function, myogenic enzymes). The goals of treatment are the following: restoration of function and relief of pain. Psychological support is advocated. Although the exact number of patients with JFM is still to be elucidated, it seems to be growing because pediatric rheumatologists in Japan encounter children with a wide variety of musculoskeletal pains. This guideline describes how to diagnose JFM in children and how to treat them appropriately.